2017
DOI: 10.2147/phmt.s115528
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the optimal management of infantile hemangioma

Abstract: Infantile hemangiomas (IHs) are the most common benign tumor of infancy. As our understanding of their pathobiology has evolved, treatment has become more focused and tailored to specifically treat IH while minimizing adverse effects. Propranolol has gained FDA approval as the first medical therapy for a traditionally surgical disease. This review provides readers with an overview of IH, treatment modalities, and addresses specific considerations in IH disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 93 publications
(133 reference statements)
1
25
0
2
Order By: Relevance
“…Beta‐blockers are known to induce involution of infantile hemangiomas and are now considered first‐line treatment for problematic infantile hemangiomas. In 2014, the FDA‐approved formulation of propranolol solution for the treatment of infantile hemangiomas for infants aging 5 weeks to 5 months . After the successful use of oral propranolol in infantile hemangiomas, topical propranolol was tried for the management of superficial hemangiomas.…”
Section: β‐Blockers In Extra‐cardiac Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta‐blockers are known to induce involution of infantile hemangiomas and are now considered first‐line treatment for problematic infantile hemangiomas. In 2014, the FDA‐approved formulation of propranolol solution for the treatment of infantile hemangiomas for infants aging 5 weeks to 5 months . After the successful use of oral propranolol in infantile hemangiomas, topical propranolol was tried for the management of superficial hemangiomas.…”
Section: β‐Blockers In Extra‐cardiac Conditionsmentioning
confidence: 99%
“…In 2014, the FDA-approved formulation of propranolol solution for the treatment of infantile hemangiomas for infants aging 5 weeks to 5 months. 70 After the successful use of oral propranolol in infantile hemangiomas, topical propranolol was tried for the management of superficial hemangiomas. A systematic review and meta-analysis of topical use of b-blockers for the treatment of hemangiomas observed that local application of bblockers can be an effective treatment option for superficial infantile hemangiomas and should be considered for primary treatment.…”
Section: Hemangiomasmentioning
confidence: 99%
“…The treatment of splenic hemangioma in children has been mostly partial or total splenectomy [ 1 , 2 ], while Islam et al reported that the use of oral prednisolone that had an effective antiangiogenic effect in a large splenic hemangioma in an infant [ 3 ]. Recently, propranolol has been used for primary therapy of infantile hemangioma; however, to our knowledge, there have been no reports of propranolol for splenic hemangiomas [ 12 ]. Further studies may be needed to determine the effectiveness propranolol for splenic hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Infantile hemangioma (IH) is a common congenital vascular malformation that affects 4–5% of full-term infants ( Itinteang et al., 2014 ; Grzesik and Wu, 2017 ). The incidence of IH is higher in females than in males, with an estimated ratio of 3–5:1 ( Harter and Mancini, 2019 ; Wildgruber et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%